2013
DOI: 10.1051/0004-6361/201322289
|View full text |Cite
|
Sign up to set email alerts
|

A search for pulsations in the HgMn star HD 45975 with CoRoT photometry and ground-based spectroscopy

Abstract: The existence of pulsations in HgMn stars is still being debated. To provide the first unambiguous observational detection of pulsations in this class of chemically peculiar objects, the bright star HD 45975 was monitored for nearly two months by the CoRoT satellite. Independent analyses of the light curve provide evidence of monoperiodic variations with a frequency of 0.7572 d −1 and a peak-topeak amplitude of ∼2800 ppm. Multisite, ground-based spectroscopic observations overlapping the CoRoT observations sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…Among main-sequence CP stars, pulsations are found at least in roAp stars, and possibly in HgMn stars which partly share the region of slowly pulsating B type (SPB) stars in the HR-diagram (Alecian et al 2009;Morel et al 2014); for roAp stars, pulsations seem to coexist with vertical abundance stratifications (see for instance Freyhammer et al 2009). It is not yet known how these pulsations interact with the atmospheric structure, and whether or not they induce weak mixing.…”
Section: Other Processesmentioning
confidence: 99%
“…Among main-sequence CP stars, pulsations are found at least in roAp stars, and possibly in HgMn stars which partly share the region of slowly pulsating B type (SPB) stars in the HR-diagram (Alecian et al 2009;Morel et al 2014); for roAp stars, pulsations seem to coexist with vertical abundance stratifications (see for instance Freyhammer et al 2009). It is not yet known how these pulsations interact with the atmospheric structure, and whether or not they induce weak mixing.…”
Section: Other Processesmentioning
confidence: 99%
“…9 and 10. For the fit performed to determine the stellar radii, we took into account the fastwind synthetic fluxes and the TD1 (for HD 47777), Johnson, and 2MASS photometry (note that we did not consider the TD1 flux value at ∼2800 Å, which is affected by systematics; see e.g., Morel et al 2014). We excluded the far-IR photometry from the fit to highlight infrared excess.…”
Section: Spectral Energy Distributionmentioning
confidence: 99%
“…Generally, CP1 stars are not expected to show rotational light variability; in relation to CP3 stars, this is still a matter of debate (Paunzen et al 2013;Morel et al 2014). Interestingly, in a recent study using ultra-precise Kepler photometry, Balona et al (2015) have found that most of the investigated Am stars exhibit light curves indicative of rotational modulation due to star spots.…”
Section: Introductionmentioning
confidence: 99%